The Role of Medicinal Plants in Domestic Animals and Estrus Induction with Particular Reference to Aegle marmelos and Murraya Koenigii - Kujur , Anju; Srivastava , N.; Jasrotia , Nancy; J , Arunpandian (Animal Reproduction Update, 2022)
Due to malnutrition and inadequate management practices, anestrus is frequently observed in domestic animal species, particularly in rural areas. This financially crippling condition in affected animals can be mitigated using available therapeutic measures. The primary challenges with employing hormones or other medicaments for animal reproductive management are the massive price, lack of rapid assay resources, barely commercially accessible and the requirement for veterinarian care. Therefore, herbal medicines are a good alternative since they are cheap, effective, and socially acceptable and they are often the only option with little side effects. Herbal combinations can have significant beneficial effects due to the synergistic or cumulative effects of their active principles. Plants have a wide spectrum of beneficial effects in their natural state and have immense potential as a source of new medications. Traditional remedies Murraya koenigii (curry leaves) and Aegle marmelos (bael) have been shown to boost reproductive performance in lab rats, anoestrus caprine and bovines.
Keywords: Anestrus; Herbal plants; Murraya koenigii; Aegle marmelos